Evaluation of the prevalence and factors associated with acute kidney injury in a pediatric intensive care unit - Cibelle Ferreira Louzada; Alexandre Rodrigues Ferreira (Elsevier, 2021)
Objective: To assess the prevalence of acute kidney injury in pediatric intensive care unit according to diagnostic criteria - pediatric risk, injury, failure, loss, end-stage renal disease, Acute Kidney Injury Network and Acute Kidney Injury Work Group, or Kidney Disease: Improving Global Outcomes -, and determining factors associated with acute kidney injury as well as its outcome. Methodology: This was a cross-sectional monocentric observational study, including patients aged between 29 days and 17 years who were admitted to the pediatric intensive care unit between January 1, 2012 and December 31, 2016. To evaluate the association between the study variables and acute kidney injury, the log-binomial generalized univariate and multivariate linear models were adjusted. Results: The study included 1131 patients, with prevalence of acute kidney injury according to the Acute Kidney Injury Network and Kidney Disease: Improving Global Outcomes criteria of 12.6% and of 12.9% according to the pediatric risk, injury, failure, loss, end-stage renal disease. In the multivariate analysis of older children (PR 1.007, 95% CI: 1.005-1.009), sepsis (PR 1.641, 95% CI: 1.128-2.387), demand for ventilatory support (PR 1.547, 95% CI: 1.095-2.186), and use of vasoactive amines (PR 2.298, 95% CI: 1.681-3.142) constituted factors associated with statistical significance to the development of acute kidney injury. The mortality rate among those with acute kidney injury was 28.7%. Conclusion: Older children, diagnosis of sepsis, demand for ventilatory support, and use of vasoactive amines were correlated with a higher risk of developing acute kidney injury. The mortality associated with acute kidney injury was elevated; it is crucial that all measures that ensure adequate renal perfusion are taken for patients with risk factors, to avoid the installation of the disease.